Subcritical crack growth, initiation, and arrest in columnar freshwater and sea ice - Parsons, B. L. (Memorial University of Newfoundland, Faculty of Engineering and Applied Science, 1990)
No subcritical crack growth was observed in either ice. All crack growth was abrupt. Arrest toughness was approximatedly 90 kNm-3/2 for both ices. Sea ice toughness was 113 ± 38 kNm-3/2, freshwater 124 ± 38 kNm-3/2. NRC publication: Yes